Tindak Tutur Representatif dalam Kumpulan Video Fakta-Fakta Hewan pada Channel YouTube Sisi Terang (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
Speech acts are communication events in which a person uses language to convey a specific message or purpose. Representative speech acts are a type of speech act that serves to state or describe the truth of something, such as facts, explanations, and descriptions. Representative speech acts themselves are steps or processes that aim to foster trust between conversation partners. Representative speech acts do not only occur in face-to-face conversations, but are also found in various contexts, such as on YouTube social media. This study aims to analyze representative speech acts in the YouTube channel Sisi Terang regarding animal facts. The method used in this study is descriptive with a qualitative approach, using listening and note-taking techniques. The data were analyzed using a literature study that required scientific journals, and the results were presented in tabular form. This study required scientific journals and a laptop as tools or aids. The research data consisted of 104 utterances taken from a collection of videos on the Sisi Terang YouTube channel. The results of the study show that there are 10 types of representative speech acts, namely stating 57 utterances, mentioning 6 utterances, showing 14 utterances, reporting 14 utterances, demanding 1 utterance, acknowledging 2 utterances, giving examples of 2 utterances, explaining 6 utterances, speculating 1 utterance, and predicting 1 utterance. This study is expected to benefit readers in understanding the meaning of representative speech acts and can be used as a reference for creating informative and accurate educational content.